2022
DOI: 10.3390/buildings12081224
|View full text |Cite
|
Sign up to set email alerts
|

Review of Mechanical and Temperature Properties of Fiber Reinforced Recycled Aggregate Concrete

Abstract: Recycled aggregate concrete has received increasing attention owing to its broad development prospects in recent years. This study discusses the enhancement mechanism of various fibers on the mechanical properties, high-temperature resistance, and freeze–thaw cycle resistance of recycled aggregate concrete. It reviews the effects of fiber types and content on the strength, failure state, and resistance to recycled aggregate concrete’s high and low temperatures. The results indicate that fibers can significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 101 publications
1
2
0
Order By: Relevance
“…In our case, the greatest ré sistance is recorded with steel fibers concrete at 600℃. Similar results were observed by Serafini et al [40] and cited by Yao et al [41]. To better understand the mechanical behavior of lightweight fiber-based concrete specimens, mechanical compressive strength tests are carried out, in which the fibers do not play an important role in the compressive strength but the fibers contribute to the tensile strength.…”
Section: Loss Of Masssupporting
confidence: 80%
“…In our case, the greatest ré sistance is recorded with steel fibers concrete at 600℃. Similar results were observed by Serafini et al [40] and cited by Yao et al [41]. To better understand the mechanical behavior of lightweight fiber-based concrete specimens, mechanical compressive strength tests are carried out, in which the fibers do not play an important role in the compressive strength but the fibers contribute to the tensile strength.…”
Section: Loss Of Masssupporting
confidence: 80%
“…A freezing and thawing environment leads to the expansion of internal pores and microcracks in the mortar, and ultimately, the specimen surface cracks through and spalls. After adding basalt fibers, the fibers are irregularly distributed in the mortar, forming a three-dimensional spatial mesh structure, which can inhibit the development of internal cracks in the mortar and can offset a portion of the freezing and expansion force generated by water icing, effectively improving the frost resistance of walnut shell mortar [64][65][66]. The freeze-thaw damage of mortar generally results from many factors.…”
Section: Change In the Relative Dynamic Modulus Of Elasticity Of The ...mentioning
confidence: 99%
“…For example, Jiao et al [16] found that a content of BF not higher than 1% can significantly improve the mechanical properties of recycled aggregate concrete. Yao et al [17] also carried out similar research based on recycled concrete. The results show that fiber can significantly improve the flexural and tensile strength of recycled concrete, but has little effect on compressive strength.…”
Section: Introductionmentioning
confidence: 97%